Multi-scale three-dimensional analysis on local arrestability of intergranular crack in high-strength martensitic steel. (1st August 2022) - Shibata, Akinobu; Gutierrez-Urrutia, Ivan; Nakamura, Akiko; Miyamoto, Goro; Madi, Yazid; Besson, Jacques; Hara, Toru; Tsuzaki, Kaneaki
Abstract: The present study investigated the local arrestability of intergranular crack in high-strength martensitic steel through multi-scale three-dimensional (3D) analysis using X-ray computed tomography and focused ion beam machining (FIB)-scanning electron microscopy (SEM) serial sectioning combined with electron backscattering diffraction (3D EBSD). Macroscopic analysis using X-ray computed tomography demonstrated discontinuous propagation of the intergranular cracks, indicating local arrest of the crack propagation. An analysis of the opening displacement of each crack component revealed that the resolved normal stress was not the only factor determining the intergranular crack propagation path. The relationship between the microstructure and local crack-arrestability was microscopically analyzed using FIB-SEM serial sectioning. The 3D EBSD analysis clearly suggested that the crack propagations were arrested at the low-angle grain boundary plane segments and at the grain boundary triple junctions surrounded by relatively large martensite variants. Moreover, the larger martensite variants around grain boundaries contributed to the plastic accommodation of stress concentration and promoted crack-tip blunting. We propose that increasing the fraction of low-angle grain boundary plane segments as well as that of large martensite variants existing around grain boundaries can enhance local crack-arrestability and retard intergranular fracture of high-strength martensitic steels. Graphical abstract: Image, graphical abstract